The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1038/sj.jes.7500488
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of use and consumption of public drinking water among pregnant women

Abstract: Disinfection by-products (DBPs) in drinking water may be associated with adverse pregnancy outcomes. However, the results from previous epidemiological studies are not consistent, perhaps in part due to individual variation in water use and consumption. This study was performed to evaluate and describe demographic and behavioral characteristics as predictors of ingested water, showering, bathing, and swimming among pregnant women. Water use and consumption data were collected through telephone interviews with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 25 publications
1
20
2
Order By: Relevance
“…In a previously published work (Forssen et al, 2007), we found that season had a strong impact on water use and consumption. Season was, therefore, adjusted for in the regression models in this study.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In a previously published work (Forssen et al, 2007), we found that season had a strong impact on water use and consumption. Season was, therefore, adjusted for in the regression models in this study.…”
Section: Discussionmentioning
confidence: 60%
“…There are several previous studies describing the variation of water use in different populations (Windham et al, 1992;Shimokura et al, 1998;Williams et al, 2001;Zender et al, 2001;Barbone et al, 2002;Kaur et al, 2004;King et al, 2004;Forssen et al, 2007), but only three have examined changes in water use during pregnancy (Windham et al, 1992;Shimokura et al, 1998;Barbone et al, 2002). Shimokura et al (1998) assessed the variation in water use based on a 3-day diary among pregnant women in the US.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas they were older and more often employed than the non-participant women, age and employment have been described as associated only with filtered tap water ingestion during pregnancy, not with total tap water ingestion. 4,10 Estimates of Water Ingestion Tap water ingestion represented 71% of total water ingestion. With similar definition of water ingestion and data collection procedures relatively similar to ours, Forssé n et al 5 7 Proportion of tap water ingestion of EDDS women seemed to be comparable to that in English-speaking countries and lower than that in other Mediterranean countries, such as Italy or Spain.…”
Section: Water-use Habits Of Pregnant French Womenmentioning
confidence: 99%
“…They comprised questions chosen following an intensive review of the literature on water-use habits (Supplementary File 4) and exposure assessment questionnaire design. 18 The questionnaires had five sections: (i) socioeconomic data, 19 (ii) medical data, (iii) history of professional exposure, (iv) dermal water exposure, 4,5,[8][9][10] (v) drinking-water and bottled water ingestion frequency, 4-6,8-10 (vi) diet questions (rate of cans, fresh fruit and vegetable consumption), (vii) alcohol and tobacco consumption and (viii) cosmetics type and use frequency.…”
Section: Recruitment and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation